Answer:
Step-by-step explanation:
In this case, you need to solve for y in y + y/a = b, if s ≠ - 1.
This is how you do it step-by-step:
1. Multiply all the equation by the common denominator: a
![y + y/a = b\\ \\ a(y + y/a = b)\\ \\ a(y + y/a) = ab](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b0a903vvn5ixq8uo7zdd7yvyt72wfdedak.png)
2. Simplify:
![ay + ay/a = ab\\ \\ ay+y=ab](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p0yzpvvmbylkgtx9ebi2mbexkso5ob2zx9.png)
3. Common factor: y
![y(a+1)=ab](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8d50eh9gr4b6nqxg6dodcft4m7zzt5wk5j.png)
4. Divide both sides by a + 1
![y=ab/(a+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z5apwcfeh7evbo8iet4970jn1szv6hbh22.png)